GWAS of Chickpea Grain Macronutrient and Lipidomic Profiles From a Global Diversity Panel - Sally Buck; Jakob Butler; Raul Ortega; Matthew Taylor; Jeni Pritchard; Jean‐Philippe Ral (Legume Science)
ABSTRACT Chickpea is an important agricultural crop with high nutritional value and potential for functional ingredient applications. Chickpeas are categorised into two market classes, desi and kabuli, according to grain size and colour, but variation in grain composition including the lipidome within and between classes remains largely unexplored. Macronutrient characterisation was performed alongside lipidomic analysis in a global Chickpea Diversity panel to identify drivers of grain composition and relationships between nutritional traits. Assays performed on chickpea flour showed extensive variation in almost every seed composition trait, with no relation to market class or geographic origin. Lipidomic analysis revealed triacylglycerols to be the most abundant lipid class in all chickpeas, regardless of market class, and C18:2 was the most abundant class of fatty acids. The analysis also identified low abundance fatty acids not previously classified in chickpeas (C20:1, C20:2, C18:4, C16:2 and C16:3). Moderate to absent correlations between macronutrient content suggest independent genetic control amenable to breeding. A genome‐wide association study (GWAS) identified several loci of interest for grain composition, with 8% of the variation in starch concentration explained by two haplotypes, providing promising avenues for future work. These results highlight important opportunities for developing chickpea varieties with enhanced nutritional profiles and better suitability for emerging markets.